2008
DOI: 10.1016/j.jjcc.2008.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of Waon therapy on patients with chronic heart failure: Results of a prospective multicenter study

Abstract: Waon therapy is safe, improves clinical symptoms and cardiac function, and decreases cardiac size in CHF patients. Waon therapy is an innovative and promising therapy for patients with CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 16 publications
1
92
0
3
Order By: Relevance
“…We have already demonstrated significant efficacy of 10-15 sessions of Waon therapy for patients with milder HF. 8,14-17, 21 However, in patients with more advanced HF, such as those enrolled in the present study, more sessions (eg, 20-40 times) of Waon therapy are likely needed to achieve apparent clinical benefits such as left ventricular reverse remodeling. Evidence supporting longterm Waon therapy in patients with advanced HF is be a future concern.…”
Section: Study Limitationsmentioning
confidence: 95%
See 1 more Smart Citation
“…We have already demonstrated significant efficacy of 10-15 sessions of Waon therapy for patients with milder HF. 8,14-17, 21 However, in patients with more advanced HF, such as those enrolled in the present study, more sessions (eg, 20-40 times) of Waon therapy are likely needed to achieve apparent clinical benefits such as left ventricular reverse remodeling. Evidence supporting longterm Waon therapy in patients with advanced HF is be a future concern.…”
Section: Study Limitationsmentioning
confidence: 95%
“…21 Patients remained seated for 15 min, and then rested supine while covered with a warm blanket for an additional 30 min. All participants were weighed before and after the Waon therapy, and oral hydration with cold water was provided to compensate for the weight loss from perspiration.…”
Section: Waon Therapymentioning
confidence: 99%
“…5 In a prospective multicenter study, we have confirmed that Waon therapy is safe, improves clinical symptoms and cardiac function, and decreases cardiac size in CHF patients. 6 Recently, we assessed the impact of Waon therapy on the prognosis of 129 patients with CHF: 64 underwent Waon therapy, 65 did not, and the patients were followed for 5 years. The patients in the Waon group continued the therapy at least twice weekly after discharge.…”
Section: Effect Of Waon Therapy On Chfmentioning
confidence: 99%
“…19) And they demonstrated that Waon therapy improved clinical symptoms and cardiac function evaluated by 2DE and BNP concentrations, and decreased cardiac size on chest radiography and 2DE after once a day, 2 weeks of Waon therapy in patients with CHF using the movable and sitting-position sauna system. 19) …”
Section: Effect Of Waon Therapy On Heart Failurementioning
confidence: 99%